The Inducing effect of lemon juice in the total antioxidants capacity, male hormones in New Zealand white male rabbits fattened experimentally - Iman M. S. Jallod; Muntaha M. Al-Kattan (Tikrit Journal of Pure Science, 2023)
This study is designed to estimate the effect of experimental fattening of New Zealand white male rabbits and then use lemon juice to show their impact on the total antioxidants capacity (TAC) and the level of the Spermatogenic Stimulating Hormone(SSH) and Interstitial Cell Stimulating Hormone (ICSH) and testosterone. Used 40 male from New Zealand white rabbits and ages ranged from 10.8 months and weights ranging from 1400-1250gm, divided into two groups of 20 rabbit/ group and putted in separate cages. Fed  the first group to standard diet, while the second group fed special diet rich in fat for the purpose of fattening for a period of 12 weeks after a period all rabbits were weighted, and divided the groups into four groups of 10 rabbit / group, are control group:, lemon Group:, fattening group and fattening with lemon Group, all these groups underwent   standard condition of water and diet, lemon group and Fattening with lemon group dosing with 4 ml/k b.wt, Lemon juice for 8 weeks where a daily dosage. The results showed that treatment with lemon juice has led to a significant increase in the level of (P≤0.0001) in each of the TAC and the level of hormones in each of lemon Group and fattening with lemon group as compared to the control group  and fattening group respectively, while the significant decrease in the level of (P≤0.0001) in (P≤0.0001) in the TAC and the concentration of hormones in fattening group compared to the control group.